From boundary‐work to boundary object: how biology left and re‐entered the social sciences. Issue 1 (21st April 2016) - Meloni, Maurizio
Abstract: In an archaeological spirit this paper comes back to a founding event in the construction of the twentieth‐century episteme, the moment at which the life‐ and the social sciences parted ways and intense boundary‐work was carried out on the biology/society border, with significant benefits for both sides. Galton and Weismann for biology, and Alfred Kroeber for anthropology delimit this founding moment and I argue, expanding on an existing body of historical scholarship, for an implicit convergence of their views. After this excavation, I look at recent developments in the life sciences, which I have named the 'social turn' in biology (Meloni, 2014), and in particular at epigenetics with its promise to destabilize the social/biological border. I claim here that today a different account of 'the biological' to that established during the Galton–Kroeber period is emerging. Rather than being used to support a form of boundary‐work, biology has become a boundary object that crosses previously erected barriers, allowing different research communities to draw from it.